A flywheel error compensation algorithm for engine misfire detection. (February 2016) - Jung, Daniel; Frisk, Erik; Krysander, Mattias
Abstract: The crankshaft angular velocity measured at the flywheel is a commonly used signal for engine misfire detection. However, flywheel manufacturing errors result in vehicle-to-vehicle variations in the measurements and have a negative impact on the misfire detection performance. A misfire detection algorithm must be able to compensate for this type of vehicle-to-vehicle variations if it is to be used in production cars to assure that legislations are fulfilled. It is shown that flywheel angular variations between vehicles in the magnitude of 0.05° have a significant impact on the measured angular velocity and must be compensated for to make the misfire detection algorithm robust. A misfire detection algorithm is proposed with flywheel error adaptation in order to increase robustness and reduce the number of mis-classifications. Evaluations using measurements from a number of vehicles on the road are used to quantify the negative impact of the flywheel errors and show that the number of mis-classifications is significantly reduced when performing on-line flywheel error adaptation.